Zoonotic Endocarditis: Is the feather mightier than the sword? - Esmail, A; Doubell, A F; Piek, H; Janson, J T; Pecoraro, A J K (SA Heart Journal, 2022)
The common causes of infective endocarditis (IE) in South Africa are Staphylococcus aureus, the viridans streptococci and Bartonella species. Infection with Erysipelothrix rhusiopathiae is a rare cause of IE that is usually associated with occupational exposure and can be acquired from humans and animals. It was fi rst reported in 1912 by Gunthar, and thereafter fewer than 60 cases have been reported. We describe a case of Erysipelothrix rhusiopathiae induced endocarditis in Cape Town, South Africa. S SAHeart 2022;19:24-27